Rearing grasscutters - Ngo-Samnick, E. Lionelle (Technical Centre for Agricultural and Rural Cooperation, 2012)
Grasscutters – large rodents commonly found in the wild in areas of grassland, clearings, wet or marshy areas in Africa – breed prolifically, grow quickly and are easy to rear. Sometimes more commonly known as ‘hedgehogs’ or ‘agouti’, their meat is high in protein and value, making their rearing an ideal alternative to poaching. This practical, user-friendly guide provides extension material for unconventional animal breeding. With liberal use of illustrations, tables and sample records, it describes how to rear grasscutters for food and for profit. Chapters cover breeding conditions, housing, reproduction, handling and feeding. Production planning and disease management are also detailed, including how to prevent disease and an overview of some possible illnesses and proposed treatments. With its illustration of costs for financial planning and a list of useful contacts, this manual provides an ideal source of information and guidance for farmers, rural communities and extension workers across the region.